Prognostic Value of SUVmax Measured by Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography with Computed Tomography in Patients with Gallbladder Cancer - Hwang, Jae Pil (Springer Berlin Heidelberg, 2013)
OBJECTIVE: The aim of this study is to investigate the prognostic value of F-18 fluorodeoxyglucose (F-18 FDG) positron emission tomography (PET)/computed tomography (CT) in gallbladder cancer patients. METHODS: From June 2004 to June 2010, a total of 50 patients with gallbladder cancer who underwent diagnostic staging with F-18 FDG PET/CT following curative or palliative treatments were retrospectively evaluated. For the analysis, all patients were classified by age, sex, maximum standardized uptake value (SUVmax), lymph node (LN) or distant metastasis, serum level of CA19-9 and CEA, type of treatment and American Joint Committee on Cancer (AJCC) stage. RESULTS: The median survival for the 50 patients was 245 days and the median SUVmax in PET/CT was 8.3 (range, 0-19.7). Patients with SUVmax < 6 survived significantly longer than patients with SUVmax ≥ 6 (median 405 days vs 203 days, p = 0.0400). On Kaplan-Meier analysis, SUVmax (p = 0.0400), stage (p = 0.0001), CA19-9 (p = 0.013), CEA (p = 0.006), LN metastasis (p = 0.0001), distant metastasis (p = 0.0020), type of treatment (p = 0.0001) were significantly associated with overall survival. Multivariate analysis study revealed that the patients with lower SUVmax measured from initial staging PET/CT (p = 0.0380), no LN metastasis (p = 0.0260), a lower stage (p = 0.026) and curative treatment (p = 0.0005) had longer survivals. CONCLUSIONS: The present study shows that SUVmax on F-18 FDG PET/CT can provide prognostic information in patients with gallbladder cancer.